2015
DOI: 10.4103/2321-1407.163422
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the effectiveness of erbium-doped yttrium aluminum garnet laser with other in house refurbishing methods for reconditioning stainless steel and ceramic brackets. An environmental scanning electron microscope and shear bond strength analysis: An in-vitro study

Abstract: Introduction Brackets can be recycled by sending them to a commercial recycling company but it is time consuming and the bracket cannot be bonded in the same appointment. Hence in-house methods for recycling of brackets would be beneficial to both the orthodontist and the patient. Aim In our study, we compared the shear bond strength of brackets after being recycled with erbium-doped yttrium aluminum garnet (ER:YAG) laser, sandblasting and the thermal method. Materials and Methods The study was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…As with laser group recycling, we discovered that it was comparable to sandblasting with 25µm alumina particles, but sandblasted brackets with 25µm alumina showed numerically higher shear bond strength than laser blow method, despite being statistically insignificant. This finding is in agreement to the study carried out by Devjee et al (2015) where the stainless-steel metal brackets recycled with sandblasting showed higher shear bond strength than the brackets recycled with laser blow method (Er-YAG). 27 This study found comparable shear bond strength between laser group and group I.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As with laser group recycling, we discovered that it was comparable to sandblasting with 25µm alumina particles, but sandblasted brackets with 25µm alumina showed numerically higher shear bond strength than laser blow method, despite being statistically insignificant. This finding is in agreement to the study carried out by Devjee et al (2015) where the stainless-steel metal brackets recycled with sandblasting showed higher shear bond strength than the brackets recycled with laser blow method (Er-YAG). 27 This study found comparable shear bond strength between laser group and group I.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement to the study carried out by Devjee et al (2015) where the stainless-steel metal brackets recycled with sandblasting showed higher shear bond strength than the brackets recycled with laser blow method (Er-YAG). 27 This study found comparable shear bond strength between laser group and group I. This is in contrary to the study conducted by P Chacko et al (2013) 17 and Mirhashemi et al ( 2018) 30 where they found Er-YAG laser (2940nm) is more efficient then sandblasting.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations